The Effect of Inflation on the Commercial Enterprise Operations of Entrepreneurs in Xayaboury district, Xayaboury Province. - THONGVANHNA, Kaykeo; SIPHANTHONG, Bounthavy; Sioudomphan, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to study the effects of inflation and the adjustment guidelines of commercial enterprises in Xayabuli City, Xayabuli Province. The results of the study found that: when there is inflation in the economic system, the overall picture is that it will affect the cost of running an enterprise, especially the cost of goods brought to market and working capital, sales of goods and services, profit from operations, money for business expansion, money for other activities, a drop in regular customers and general customers, and there is a temporary stop of commercial enterprise operations or a permanent stop of commercial enterprise operations and transfer of rights to other persons. By testing the relationship between the inflation of trade in Xayaburi, the information is affected by the enterprises, but the inflation has an impact on the enterprises. Intermediate and severe inflation affects the procedure of statistical importance of 0.01; the sale of goods and services in statistical importance of 0.1; and the number of enterprise customers, stopping statistically at least 0.1 importance activities. Adapting guidelines in entrepreneurship enterprises when the entrepreneurial economic system reduces financial information, reduces the money the price of goods is compatible with consumers, with other occupation income, and with avoiding a loan issue or debt in middle-level inflation.